Effect of Hexagon Fraud Against Financial Statement Fraud with Company Size as Moderation - Akbar, Taufik; Mappadang, Agoestina (International Journal of Managemen Analytics (IJMA), 2024)
This research aims to determine the effect of hexagon fraud with company size moderating its effect on financial statement fraud. Hexagon fraud is measured through six components, namely, stimulus, capability, collusion, opportunity, rationalization and ego. Meanwhile, company size is measured through total assets and financial statement fraud is measured through the Beneish M-Score model. This research is included in descriptive quantitative research. Through purposive sampling, 35 companies were determined as samples for a 5-year observation period from a total population of 113 non-cyclical consumer sector companies as of 2022 listed on the Indonesia Stock Exchange. Data were processed using multiple linear regression. Based on the results of data analysis, it is known that partially hexagon fraud has a significantly positive effect on financial statement fraud, while company size has no effect on financial report fraud. As a moderator, company size can strengthen the influence of hexagon fraud on financial statement fraud. Simultaneous testing shows that hexagon fraud and company size influence financial statement fraud. However, both of them were only able to explain 9% of financial statement fraud with the rest explained by other variables.